نحو إطار إحصائي لقياس التدفقات المالية الضريبية والتجارية غير المشروعة - UN Trade; Development (United Nations)
This paper focuses on efforts by eleven African countries to measure tax and commercial IFFs. It reviews and assesses development of concepts and methods, and their pilot testing. As such, it draws from existing work and documents of custodian agencies and provides (further) methodological inputs into ongoing development of suggested statistical methodologies to measure tax and commercial IFFs and feed into global reporting on SDG indicator 16.4.1.